Métodos de Termometria Não Invasiva em comparação ao Método de Aferição da Temperatura de Cateter de Artéria Pulmonar: um estudo de medidas repetidas - Rafael Lima Rodrigues de Carvalho (2019)
The identification of body temperature is an essential tool in critical care nursing. The use of a reliable and agile thermometer is necessary to identify the real body temperature. When available, invasive thermometer are indicated for its precision. Although, when not available, the nursing staff must rely in noninvasive thermometers. Nowadays, in the literature, there isn´t a consensus about the reliability of noninvasive temperature techniques, such as axillary, oral, tympanic membrane and temporal artery. Furthermore, there is a lack of knowledge about factors that alters the reliability of those thermometers. Clinical studies must be developed to back these techniques in nursing care. Aim: Compare the accuracy and precision of noninvasive techniques (axillary, oral, tympanic membrane and temporal artery) with the pulmonary artery temperature. Methods: An Systematic review/Metanalysis and a Cross-sectional Repeated measure clinical study were developed. The Metanalysis used data from 41 published articles. The data for the clinical study were collected in two intensive care units of two hospitals in Belo Horizonte. Patients with pulmonary artery catheter were included. The five temperatures were measured three times in each patient. Descriptive analyses were made, Bland-Altmann graphics were plotted and a four regression models were developed. Results: The accuracy and precision identified in the Metanalysis were: axillary, -0,35 and 0,06; oral, -0,21 and 0,08; tympanic membrane, -0,05 and 0,05; and temporal artery, -0,22 and 0,26. The accuracy and precision of the noninvasive thermometers and the pulmonary artery temperature identified in the clinical study were: axillary -0,42 and 0,59; oral -0,30 and 0,37; tympanic membrane -0,21 and 0,44; and temporal artery -0,25 and 0,61. Conclusion: The noninvasive thermometers showed a good accuracy and precision when compared with the pulmonary temperature, However, in non-normothermic patients the reliability of the thermometers is poor.